RED BLOOD PROFILE OFPangasius hypophthalmusTHAT WERE FED WITH TURMERIC EXTRACT (Curcuma domestica V.) - Dede Kurnia Islami; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in September until November2017 in Parasites and Fish Disease Laboratory and an Experiment of Marine and Fisheries Faculty of Riau Universit. The aim of this research was to know the red blood profile of Pangasius hypophthalmusthat were given turmeric extract (Curcuma domestica V.) and to find out the best dosage of turmeric extract (Curcuma domestica V.) to increase the survival rate ofPangasius hypophthalmus. The method used was an experimental method with a Completely Randomized Design (CRD), with one factor and four treatments.The treatments used as control (P0) (without turmeric extract)P1 (0,5 g/kg of feed were fed with turmeric extract), P2 (0,7 g/kg of feedwere fed with turmeric extract), and P3 (0,9 g/kg of feedwere fed with turmeric extract). The results shown that feeding containing turmeric extract (Curcuma domestica V.) during 60 days of raring daysmay effect to the blood picture of Pangasius hypophtalmus. The best treatments of this research was P2 with total of erythrocyte 1,57-1,76 x106cell/mm3, haemoglobin8,6-8,7 g/dL, hematocrit 24,66% and survival rate 92%.Keywords:          Curcuma domestica V, Pangasius hypophtalmus, Erythrocyte, Haemoglobin, Hematocrit